Selective Oxidation of Benzylic Alcohols with Molecular Oxygen Catalyzed by Copper-Manganese Oxide Nanoparticles - Ali, Roushown; Assal, M.E.; Al-Warthan, Abdulrahman; Rafiq H. Siddiqui, M. (Asian Journal of Chemistry, 2013)
The catalytic activity of copper-manganese (CuMn) mixed oxide nanoparticles (Cu/Mn = 1:1) prepared by co-precipitation method has been studied for the selective oxidation of benzyl alcohol and its derivatives to the corresponding aldehydes using molecular oxygen as an oxidizing agent. A 100 % conversion of the alcohols was achieved with high selectivity (>99 %) to the corresponding aldehydes within a short reaction period at 102 ºC. The best catalytic activity was obtained for the CuMn mixed oxide pre-calcined at 300 ºC. The catalytic performance is also obtained to be dependent on the electronic and steric effects of the substituents present on phenyl ring. The catalyst has been characterized with a combination of various characterization techniques.